LOCATION SELECTION STUDY FOR THE FISH LANDING BASE IN KUALA TERUSAN VILLAGE PANGKALAN KERINCI SUB-DISTRICT PELALAWAN DITRICT RIAU PROVINCE - Arni Agusta; Syaifuddin Syaifuddin; Bustari Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on 26 April until 07 Mei 2018 in Kuala Terusan Village Pangkalan Kerinci Sub-district Pelalawan District Riau Province. This reasearch aim to determine the best location from the toke’s port site to be the place of landing fish, based on comparison from the other place so can build a fishing port at Kuala Terusan Village. The results of the analysis show that the location of port A is the best location to build a fishing port with score 230,12 point. Based on technical reviews of potential fisheries, socio-economic people, facilities and infrastructure of port A, its can meets the technical and operational criteria of a type D fishing port or called the Fish Landing Base (PPI). Keyword : Selection location, the fishing port, Kuala Terusan Villlage